Sistem Monitoring Debit dan Tingkat Kekeruhan Air Pada Kolam KOI Berbasis Mikrokontroler - Wahyu Budiman; Ratna Aisuwarya (JITCE (Journal of Information Technology and Computer Engineering), 2022)
This system aims to make it easier for owners to monitor the condition of the koi pond, and minimize the death of koi fish, and can maintain water quality and maximize koi growth and development. Therefore, a system was created that can monitor the discharge and the level of turbidity of water in the koi pond. This system consists of Arduino Uno, NodeMCu, Waterflow Sensor, Turbidity Sensor and buzzer. This system can determine the condition of the pump, whether the pump is running maximally, the signal is not optimal or the pump off based on the water flow produced by the pump, which is then read by the waterflow sensor. When the water discharge > 40 L/hour then the pump turns on maximum, when 40 L/hour > discharge > 0, then the pump flame is not maximal, and when there is no water discharge produced by the pump then the pump is off, if the water turbidity value > 400 NTU, then the water is in a cloudy state and the buzzer as an alarm so that the owner checks the filter and the pool drain will sound, and later the data read by the sensor will be saved to the firebase and will be displayed on the mobile application, and tegram will send a notification in the form of a short message , when the pump is not running optimally, the pump is off, and when the water is cloudy.